2009
DOI: 10.1002/bit.22364
|View full text |Cite
|
Sign up to set email alerts
|

Cell density effect in the baculovirus‐insect cells system: A quantitative analysis of energetic metabolism

Abstract: The cell density effect (i.e., the drop in the specific productivity in the baculovirus-insect cells expression system when cells are infected at high cell densities) has been extensively described in the literature. In this article, a model for the central metabolism of serum-free suspension cultures of Spodoptera frugiperda Sf9 cells is proposed and used to investigate the metabolic basis for this phenomenon. The main metabolic pathways (glycolysis, pentose phosphate pathway, tricarboxylic acids cycle, gluta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
107
1
7

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 115 publications
(130 citation statements)
references
References 51 publications
(130 reference statements)
15
107
1
7
Order By: Relevance
“…However, the consumption rate of infected cells at the low ICD was significantly higher than that at the high ICD at the later stage of infection, 24-60hpi (Table 4.3). The consumption rate of infected Sf9 cells in the current study was similar to that reported by Bernal et al (2009), andWong et al (1994), whereas, the glucose consumption rate for uninfected Sf9 cells (25.6×10 -12 mmol/ cell/hour) was lower than most values reported in the literature. The discrepancy in the glucose consumption rate on a per cell basis among the literature may result from the differences in cell size.…”
Section: B 42 B) Were Typical For Racmnpvsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the consumption rate of infected cells at the low ICD was significantly higher than that at the high ICD at the later stage of infection, 24-60hpi (Table 4.3). The consumption rate of infected Sf9 cells in the current study was similar to that reported by Bernal et al (2009), andWong et al (1994), whereas, the glucose consumption rate for uninfected Sf9 cells (25.6×10 -12 mmol/ cell/hour) was lower than most values reported in the literature. The discrepancy in the glucose consumption rate on a per cell basis among the literature may result from the differences in cell size.…”
Section: B 42 B) Were Typical For Racmnpvsupporting
confidence: 86%
“…4.7) for the high ICD in comparison with that for the low ICD cases. Glucose consumption rates for uninfected and baculovirus infected Sf9 cells have been extensively reported in the literature (Benslimane et al, 2005;Bernal et al, 2009;Kamen et al, 1996;Radford et al, 1997;Raghunand and Dale, 1999;Rhiel et al, 1997;Wong et al, 1994), but the values vary considerably, possibly due to cell size differences reported for the Sf9 cell line used. The consumption rate varied in the range of 4.52-12×10 -11 and 2.07-24.2×10 -11 mmol/cell/hour for uninfected and infected Sf9 cells propagated in Sf900™II medium, respectively.…”
Section: B 42 B) Were Typical For Racmnpvmentioning
confidence: 99%
“…Thus, the cells are known to produce significant amounts of lactate when suffering oxygen limitation [12]. Here, lactate formation can be detected in both the uninfected and the infected HFM cultures (Figure 6).…”
Section: Bves In Shear-free Environmentmentioning
confidence: 81%
“…According to this phenomenon, the metabolism of the insect cells is downregulated, when the cells are kept at high density [12,58].…”
Section: Bves In Shear-free Environmentmentioning
confidence: 99%
See 1 more Smart Citation